ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN KONTRASEPSI METODE KONTRASEPSI JANGKA PANJANG (MKJP): - Hidayah, Nurul; Novita Dewi Iswandari (Midwifery And Complementary Care, 2023)
Background: According to the BKKBN in 2020, the use of non-hormonal contraceptives using IUDs was 1,814,158 (8.51%), MOW 556,447 (2.61%) and in 2021 using IUDs (2.93%) and MOW  (1.59%). Based on data at RSUD Dr. H Moch Ansari Saleh Banjarmasin in 2020 (20.1%) and 2021 (54.1%) the increasing use of the Post Placenta IUD. Objective:. Identify and analyze age, parity, education, occupation and type of delivery. Methods: This study uses a quantitative method. Data collection techniques using case control and secondary data.Result: The results showed that the parity was in multiparas (64.8%), the highest education was in high school education (47.7%), and the most common type of delivery was SC delivery (48.52%).Conclusion: There is education there is a relationship with the use of the Post Placenta IUD with a p value of 0.008 and there is a relationship between the type of delivery and use of the Post Placenta IUD with a p value of 0.001. Keywords: Post Placenta IUD, Parity, Education, Type of Labor